أحكام المريض في الفقه المالكي الطهارة أنموذجا - فريجات, عائشة; - قزي, هيام; - قسوس, شيماء حفصة (University of Eloued-جامعة الوادي, 2018)
كاف ىذا البحث بر عن اف "أحكا ابؼ ض في ال قو ابؼالكي-الط ارة أبم جا-" عافً الإشكالية الآتية: ا دل اعتبار ابؼذىب ابؼالكي لأح اؿ ابؼ ض يما تعلق بباب الط ارة كقد احت ل على ثلاث باحث، ابؼبحث التم يدم : التع ف بابؼصطلحات البحث ثم ابؼبحث الأكؿ: أحكا تتعلق ب ء ابؼ ض كغسلو ثم ابؼبحث الثاني: أحكا تتعلق بتيمم ابؼ ض كخلصنا في نها ة البحث إلى نتيجة أساسية كىي: أنو ىناؾ ن عاف للعذر الذم سقط عو ال ء كالغسل ع كج د ابغدث كالنجس كلا عيد للم قة: عذر دائم كعذر غتَ دائم كفي الأختَ ن صي باستكماؿ ا بقي ن ابؼسائل ابؼ مة ابؼتعلقة بط ارة ابؼ ض حيث بوتاج ىذا ابؼ ع ى زً دان ن الاطلاع. Research Summary: This research was under the title of "patient judgments in the Maliki jurisprudence - purity is a model -" addressed the following problematic: how much the Maliki's view of the conditions of the patient with regard to the door of purity and contains three topics, the introductory section: the definition of terms research and then the first topic: The patient and his laundry and then the second topic: provisions related to Taimm patient and concluded at the end of the search to the basic result is: There are two types of excuse that falls with ablution and washing with the presence of the event and defilement does not restore hardship: a permanent excuse and excuse non-permanent and in the latter recommend the completion of the remaining important issues Related to the purity of the patient This issue needs further consideration.
مذكرة ليسانس
Keywords: المريض /الطهارة /الفقه المالكي; Patient/pureté/jurisprudence Maliki